EFFECT OF TOURISM ON ECONOMIC GROWTH IN MAMUJU DISTRICT IN REGIONAL AUTONOMY - FitrahHardiansyah, Muh.; H. , Cepi Pahlevi; RabinahYunus (International Journal of Psychosocial Rehabilitation, 2020)
Mamuju As the Capital Region of West Sulawesi Province, in this case, is a district that is developing temporarily from all sides of the economy, where one of them is in the field of tourism, which until now still has no effect on the economy, so that in the context of the implementation of Regional Autonomy the mamuju district has the opportunity to be able to explore the potential that can contribute to economic growth, especially in the field of tourism so that this journal discusses where the INFLUENCE OF TOURISM ON ECONOMIC GROWTH IN THE REGIONAL AUTONOMY ERA IN MAMUJU REGENCY in connection with that in this study aims to determine whether or not there is an influence on the relationship between the ECONOMIC GROWTH the rate of economic growth and tourism income in the Mamuju Regency. So this study uses a quantitative analysis method with a focus on testing hypotheses using SPSS 2.0 software.